? De novo Synthesis of Streptolysin S (SLS): Short Communication - MEMON, BADARUDDIN A.; BIRKBECK, T.R.; FREER, JOHN H. (Biological Sciences - PJSIR, 1994)
rial obtained from 'cells A' but at no higher dilutions, whereas a titre of 1000 HU/ml was found in material obtained from 'cells B' which was suspended in induction buffer without added chloramphenicol (Table 1).